Factors that affects Agromas products in terms of brand equity based on retailers perspective at FAMA Tangkak / Khairul Bariah Sharifpuddin - Sharifpuddin, Khairul Bariah (Faculty of Business and Management, 2010)
FAMA has introduced the Agromas brand to promote agro products that have the potential for the domestic and export markets. The market shares of Agromas product in FAMA Tangkak was increased every year. It shows that SMI’s products are more acceptable nowadays in the market. The objective of the study is to know the level of brand equity for Agromas products at FAMA Tangkak, to determine the level of brand equity for Agromas products at FAMA, to identify the relationships between factors that affects toward brand equity, to determine the most influence factors that affects Agromas products in terms of brand equity, to identify the correlations between factors toward brand equity and to identify recommendation to improve Agromas products in terms of brand equity in FAMA Tangkak. The results of the research were obtained by using six methods which was reliability test, frequency distribution, hypothesis testing, chi-square, correlation analysis and backward regression. The process of analyzing and interpreting of the data was presented through tables. All the objectives of this study had been achieved.